The impact of the implementation of the European Energy Performance of Buildings Directive on the European building stock: The case of the Cyprus Land Development Corporation. (December 2017) - Fokaides, Paris A.; Polycarpou, Kyriacos; Kalogirou, Soteris
Abstract: The building sector constitutes one of the three major energy consumers. To this end it comes as no surprise the fact that initiatives and policies in the field of energy saving focus on this sector in order to improve the energy performance of societies. The reduction of the energy consumption of dwellings becomes more important when social housing buildings are discussed, not only due to the fact that they constitute a major part of the European building stock, but also because the main concept of these buildings is that they are used by low income or vulnerable social classes. The main aim of this study is to discuss the impact of the implementation of the energy performance of the EU buildings Directive on the energy performance of the Cyprus Land Development Corporation buildings, which is the main social housing association of Cyprus. For this purpose the building stock of the corporation was studied, and detailed analysis of the actual performance and of the structural and thermal features of the considered dwellings was performed. This study produced well justified conclusions concerning the decrease of the energy consumption of Cyprus social housing corporation buildings, as well as important findings concerning the appropriate indicators which should be used in the case of the analysis of buildings energy performance. Further findings of this study include the considerations of the end-energy use for the reliable comparison between the energy habits and the lifestyle of social housing occupants, and the importance of exploiting social housing buildings both for proving the effectiveness of building related energy policies, as well as to introduce novel future relevant policies. Highlights: Impact of EPBD implementation on the energy performance of the social housing buildings. Reduction of end-energy consumption by 60% for new buildings and 30% 2000-07 buildings. Housing associations buildings should be used as model case studies. Energy consumption per area per year (kWh/m 2 a) does not consider buildings usage. Energy consumption per capita per hour of building occupancy, delivers more reliable results.